The Contribution of Near-Surface Geophysics for the Site Characterization of Seismological Stations - John D. Alexopoulos; Spyridon Dilalos; Nicholas Voulgaris; Vasileios Gkosios; Ioannis-Konstantinos Giannopoulos; Vasilis Kapetanidis; George Kaviris (Applied Sciences, 2023)
The Athenet network is the network of the Seismological Laboratory of the National and Kapodistrian University of Athens. We present the geophysical investigation that has been carried out at six seismological stations of the Athenet network for their site characterization. More specifically, at the location of each seismological station, four geophysical methods have been carried out: Seismic Refraction Tomography (SRT), Multichannel Analysis of Surface Waves (MASW), the Horizontal to Vertical Spectral Ratio (HVSR) technique, and Electrical Resistivity Tomography (ERT). The applied geophysical survey provided important information regarding the site characterization at the selected seismological stations, including key parameters such as the fundamental frequency fo, the shear-wave velocity VS, the average shear-wave velocity for the upper 30 m depth (VS30), the seismic bedrock depth, the soil type, and the subsurface geology. Moreover, selected elastic moduli (Poisson’s ratio, shear, bulk, and Young moduli) have been calculated. The site characterization information contributes to the determination of the amplification factors for each site that can lead to more accurate calculation of Peak Ground Acceleration (PGA) or Peak Ground Velocity (PGV) and, therefore, trustworthy Probabilistic and Stochastic Seismic Hazard Assessments. The derived fundamental frequency for the seismological stations of VILL, LOUT, THAL, and EPID have been determined to be equal to 10.4, 2.7, 1.4, and 7.1 Hz and their amplification factors to be 1.9, 3.1, 1.7, and 2.6, respectively. For stations MDRA and ATAL, these parameters could not be determined.